Gustav Klimt - interiors - Natter, Tobias G. 1961- (Prestel, 2023)
Interior design was extremely important to Gustav Klimt, and many of his paintings were suited to specific settings. That aspect of his work comes beautifully to life in this book. It illustrates how some of the artist’s most beloved canvases appeared in private homes and public exhibition spaces. Works such as the much-admired portraits of Adele Bloch-Bauer, Emilie Flöge, and Sonja Knips, shocking allegories such as Nuda Veritas and Hope I, and verdant landscapes are shown as they appeared in situ during Klimt’s lifetime. Full-color reproductions of the Klimt paintings are juxtaposed with historic black-and-white photographs documenting the original interiors with the featured paintings overlaid in color. Thoughtful and personal texts by Klimt scholar Tobias G. Natter accompany each major painting, providing valuable notes about the origin and context of the works, their settings, and Klimt’s early collectors and patrons. Meticulously produced and packaged, this book provides a refreshing perspective on Gustav Klimt, his networks, and his artistic vision, which made him the epitome of Viennese modernism
Keywords: Klimt, Gustav -- 1862-1918; Innenarchitektur; Malerei; Bildband